PENDAMPINGAN PENYUSUNAN MANUAL SISTEM JAMINAN PRODUK HALAL DAN DIGITAL MARKETING DI MASA PANDEMI COVID-19 - Tiara amanda Lestari; Jumiono, Aji (Universitas Djuanda, 2021)
Pandemic of Covid-19 has had a several impact on the sector of Mikro Unit Business, especially food and beverage. Social restrictions encourage the acceleration of the digital marketing economy to increase sales. The ownership of business licenses such as halal certificate has also been proven to increase consumer preferences to buy and increase profits in the long term, especially during pancemic covid 19. The Micro Unit Business that be targeted to be accompanie by the preparation of manual SJPH and digital marketing is UMK KRIPIKA Caringin Bogor which production cassava chips with original flavor, balado, barbeque and sweat corn as well as processed mustofa potatoes. This internship is carried out for 6 weeks. Prosedure steps for this internship begin with training on the Halal Product Assurance System and Digital Marketing assistance using Canva and Shopee aplications. The end result of this activity is UMK KRIPIKA has compiled manual SJPH that can be used as a requirement for registering halal certification, has the ability to design advertisments using Canva and is able to manage store on marketplace such as Shopee application